I'm A Celebrity ... Get Me Out of Here! : The Inside Story - Busk-Cowley, Mark (London Bantam Press, 2014)
Have you ever wondered how the Bushtucker Trial is dreamed up? Or what Ant and Dec's daily routine is when they are filming the show? ... Packed with behind-the-scenes secrets and ... photos from the [British version of] the show ... You'll hear from the stars who have called the jungle their home, meet the people who make it all happen and get the juiciest gossip from thirteen unforgettable series.
Include Color Illustrations.
The Inside Story.
Keywords: I'm a celebrity, get me out of here -- Television program